Addressing the messiness of data analysis: Praxis, readiness and tips from doctoral research. Issue 2 (4th March 2019) - Sakata, Nozomi; Christensen, Carly; Ware, Hannah; Wang, Sihui
ABSTRACT: Despite the fluid and nonlinear nature of data analysis, specifically in qualitative research, published work in comparative education has rarely discussed the messy aspects of data analysis. This Forum addresses the complexity of the analysis stage faced by three doctoral researchers in terms of: considering data analysis when selecting data collection tools; messiness of data analysis deriving from fieldwork and data collection; integrating different data sources; practising reflexivity during data analysis; and ethical issues arising from data analysis. The Forum aims not only to offer suggestions and tips to deal with data analysis but also to encourage more open discussions on this topic within the research community.